Social Mobility Analysis of Fruit-Sellers in Makassar City, Indonesia - yumriani; Samsuriadi; St. Haniah; Abdul Aziz Muslimin; Muhammad Nawir; M. Asri Tapa (UPT Publikasi Ilmiah (Universitas Islam Bandung), 2025)
Abstract. The growth of Makassar City with more comprehensive trading activities indicates business activity. Fruit-sellers as a form of business on the side of the road (street vendors) still exist with the challenges of advancing other business patterns. The existence of fruit traders is caused by their ability to achieve economic benefits and better social status. This study focuses on the social mobility of fruit-sellers as indicated by their accessibility to information, business, basic needs, and social interaction. Study with a quantitative approach involving 82 respondents with various criteria that meet the research requirements. The analysis results show that the social mobility of fruit-sellers is in the high category, characterized by the ability to interact socially and fulfil the family's basic needs. In comparison, business accessibility and the use of information technology are in the medium category. They tend to be in a low category. These results indicate that fruit traders must strive to increase their business capacity in terms of expanding business space and mastering information technology.